QIṢAṢ AL-ĀBĀI WA AL-ABNĀI FĪ AL-QURĀN AL-KARĪM WA ĀṠARUHĀ FĪ TARBIYAH AL-ABNĀI: DIRĀSAH MUQĀRANAH BAINA QIṢATAY NUḤ MA’A IBNIHI WA IBRĀHĪM MA’A IBNIHI - Ramadhani, Wali; Gumi, Sulaim Sulaiman; Humaira, Dara (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2021)
The stories of the Quran are one of the interesting topics in the Quranic studies. Every story in the Qur'an contains various wisdom and lessons. One of the stories mentioned in the Quran is the story of parents and children. In this article, the author presents two stories of parents and children in the Koran, namely the story of Prophet Nuh As. and his disobedient son and the story of Prophet Ibrahim As and his son who was pious and devoted to his parents, namely Prophet Ismail As. This study uses a descriptive-analytical method. Using this Method, the author gathered Quranic verses relating to two stories and subsequently elaborated and analyzed the wisdoms on child education contained in the stories. Based on this method there are several research results: First; The story of Nuh As and his son showed us the distinct behavior of humans. Prophet Nuh As represents a father who believes and responsible on his Child’s education, while his son, Kan'an represents a child who is disbelieving and disobeying to his father. Second; The story of Prophet Ibrahim As and his son, Prophet Ismail as showed us a strong relationship between a father and his son. Prophet Ibrahim as represents a father who is faithful and responsible on his child’s education, while Prophet Ismail as represents a child who is faithful, tough and strong. Third; Some aspects of education in child care based on these two stories are faith education (the first education that must be given to children) and moral education, which is a reflection of faith education. This moral education will be achieved by three elements, namely in the form of exemplar, advice and environment.